Reelin Immunoreactivity in the Adult Spinal Cord: A Comparative Study in Rodents, Carnivores, and Non-human Primates - Krzyzanowska, Agnieszka; Cabrerizo, Marina; Clascá, Francisco; Ramos-Moreno, Tania (Frontiers in Neuroanatomy, 2020)
Reelin is a large extracellular matrix glycoprotein secreted by several neuronal populations in a specific manner in both the developing and the adult central nervous system. The extent of Reelin protein distribution and its functional role in the adult neocortex is well documented in different mammal models. However, its role in the adult spinal cord has not been well characterized and its distribution in the rodent spinal cord is fragmentary and has not been investigated in carnivores or primates as of yet. To gain insight into which neuronal populations and specific circuits may be influenced by Reelin in the adult spinal cord, we have conducted a light and confocal microscope study analysis of Reelin-immunoreactive cell types in the adult spinal cord. Here, we describe and compare Reelin immunoreactive cell type and distribution in the spinal cord of adult non-human primate (macaque monkeys, Macaca mulatta), carnivore (ferret, Mustela putorius) and rodent (rat, Rattus norvegicus). Our results show that in all three species studied, Reelin-immunoreactive neurons are present in the intermediate gray matter, ventricular zone and superficial dorsal horn and intermedio-lateral nucleus, while positive cells in the Clarke nucleus are only found in rats and primates. In addition, Reelin intermediolateral neurons colocalize with ChAT only in macaque whilst motor neurons also colocalize Reelin and ChAT in macaque, ferret and rat spinal cord. The different expression patterns might reflect a differential role for Reelin in the pathways involved in coordination of locomotor activity in the fore- and hind limbs.